Manual of urodynamics for gynaecologists - Dolan, Lucia; Thakar, Ranee; Toozs-Hobson, Philip M. (Cambridge University Press, 2020)
This manual is a concise, straightforward guide for learning how to perform high-quality urodynamic investigations. Experienced editors and contributors provide easy-to-follow practical information on pre-test assessment of urodynamic function, how to set up urodynamic equipment, and how to perform individual urodynamic techniques, including cystometry, videocystourethrography and ambulatory monitoring. The book covers modern equipment and its use, and outlines the new national standards in urodynamics, allowing readers to check their knowledge and standard operating procedures are adequate. It also gives valuable information on how to set up and run a urodynamics service. With clear illustrations and clinical case studies woven into the text, this is a must-have resource to facilitate training in urodynamics. It is also a refresher of the standards and protocols required for good urodynamic practice for gynaecologists and continence nurses.